Sistema de cultivo mixto en jaulas y estanques para el pejerrey Odontesthes bonariensis - Colautti, Darío César (2009)
In the last years pejerrey culture has been developed in an intensive form using circular tanks. Employing this system is possible to obtain fish of commercial size but the production costs are high making this activity not profitable. An alternative to reduce costs is to rear pejerrey employing a mix system using cages in natural lagoons anda posterior culture in tanks until commercial size (250g). In a first step, pejerrey fish hatched and reared for 25 days at IIB-INTECH aquaculture facilities were transferred to floating cages of 16 m3 (50 fish/m3) placed at Lacombe Lagoon (Chascomús County). After 11 months, and only eating natural food, these fish had a total length (TL) of 15 ± 0.19 cm and a weight of (W) 25.27 ± 1.5 g. During this period of time the mean survival was 18 %. Then, 400 fish were transported to the IIB-INTECH and placed in an outdoor tank of 20.000 liters with an open water flow system and a salinity of 15 g/L. They were fed twice a day to satiation with artificial diets designed for pejerrey. After 26 months posthatching the fish had a TL of 30.66 ± 0.65 cm and a weight of 254.79 ± 9.72 g. During this period the mean water temperature was 18 °C and the survival was around 95 %. Taking together these results we conclude that is possible to rear pejerrey in a mix system until the commercial size in 26 months, reducing the costs of the first year. This method also gives the possibility to produce juveniles in a cheap way or to grow pejerrey up to commercial size as independent activities.